From Legal to Customary Approach: Seeking an Alternative Policy on the Coastal Area Solid Waste Management in Jambi, Indonesia - Sagala, Irmawati (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
The waste issue in coastal areas is an important and urgent problem for maritime regions like Indonesia. The task of the government in coastal areas is more complex than in mainland areas because the problem of coastal waste is more complex, and it causes more environmental impacts. This article analyzes waste management policies in the coastal areas of Jambi Province, especially in East Tanjung Jabung Regency. The research uses literature study as the primary method, supported by qualitative field studies on government and community paradigms on waste management regulations. The study shows that the East Tanjung Jabung Regency Government has a waste management policy, but none specifically concerns coastal or marine waste. However, the waste management program in the coastal area has not been implemented due to various technical reasons, especially geographical conditions, which are difficult to reach from the district capital. These constraints are caused by the positive regulation paradigm, in which the laws in Indonesia are hierarchically stopped at the district/city level so that waste management work is concentrated in the district government. The village government has the right to issue village regulations, but innovation in village regulations still needs improvement, especially in Jambi Province. This condition allows the decision maker to uphold the customary approach as a local alternative policy.Â Â